Study of Impact of New Butwal-Gorakhpur 400Kv Transmission Line on the Operation and Reliability of INPS - Yadav, Gopal Kumar; Karki, Nava Raj; Gautam, Basanta Kumar (Journal of Advanced College of Engineering and Management, 2024)
In recent years, the significance and imperative of conducting impact studies on grid reliability evaluation have escalated. This thesis represents load flow analysis with a focus on improving resilience and efficiency after adding new Butwal-Gorakhpur 400KV cross border transmission line to existing power system of Nepal and simulation of 2028A.D. INPS network to find the reliability indices. The INPS is facing unprecedented challenges brought about by the increasing demand for electricity, the integration of hydropower and renewable sources, and the need for enhanced system reliability. This thesis reviews the current state of power systems and the challenges they face, including capacity constraints, energy losses. In this context, the integration of NB-G 400KV transmission line has emerged as a promising solution to address these challenges. The core of this research are used to assess the potential benefits, such as increased grid capacity, reduced transmission losses, improved power quality and reliability of the system after the integration of New Butwal-Gorakhpur (NB-G) line. Load flow analysis is carried out in DIgSILENT to find out system loss, voltage profile and reliability indices.